Personal Branding Youtuber Topik Sudirman pada Media Sosial Youtube - Saputro, Dwi; Santoso, Budi (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study examines the process of developing the personal branding of YouTuber Topik Sudirman through his YouTube account. In today's digital age, social media has emerged as a new form of communication that is widely used for conversation, information sharing, and as a platform for branding and creative expression. Personal branding is defined as the process of enhancing the public's positive perception of a person's qualities, abilities, or character. This study employs a qualitative approach using the case study method, with data collected through observation, documentation, and interviews. Using purposive sampling techniques, the research informants were identified as Topik Sudirman as the primary informant and subscribers as secondary informants. Erving Goffman's impression management theory serves as the primary analytical tool in this study. In this study, constructivism serves as the paradigm. The findings of this study indicate that Topik Sudirman develops his personal brand using music, personal stories, and emotionally charged content, inspired by influencers who encourage external research. I am not limited to a specific type of content, so I can freely express myself through music, vlogs, and podcasts. Consistency in watching videos is based on the quality and relevance of the content, not just frequency. Financial and career benefits are supported by personal branding. According to Goffman's impression management theory, Topik Sudirman has successfully presented himself as honest, emotional, and authentic on YouTube.